Laboratory tools for tuberculosis control in a setting with a high burden of HIV/AIDS. Issue 11 (9th October 2019) - Reis, Ana J.; Diniz, Jaciara L. C. G.; Silva, Ana B. S.; Silveira, Jussara; Basso, Rossana; Vieira, Roseli; von Groll, Andrea; Ramis, Ivy B.; da Silva, Pedro E. A.
Abstract : Introduction. Nosocomial transmission of Mycobacterium tuberculosis is an important health issue and the detection of tuberculosis (TB) cases is the main tool for controlling this disease. Aim. We aimed to assess the possible occurrence of nosocomial transmission of M. tuberculosis in a reference hospital for HIV/AIDS patients and evaluate both the performance of the Xpert MTB/RIF (Xpert) platform and drug resistance profiles. Methodology. We evaluated the performance of the Xpert platform. Samples that tested positive on the BACTEC MGIT 320 (MGIT320) platform were submitted for genotyping and drug susceptibility testing. Results. In this study, pulmonary and extrapulmonary samples from 407 patients were evaluated, and among these, 15.5 % were diagnosed with TB by the MGIT320 platform, with a TB/HIV coinfection rate of 52.4 %. The Xpert platform gave positive results for TB for 11 samples with negative results on the MGIT320 platform. In the genotyping results, 53.3 % of the strains clustered; of these strains, half were in two of the four clusters formed, and the patients had visited the hospital on the same day. Drug resistance was observed in 11.7 % of the strains. Conclusion. Putative nosocomial transmission of M. tuberculosis was detected, showing that genotyping is a powerful approach for understanding the dynamics of M. tuberculosis transmission, especially in a high-burden TB and HIV landscape.